KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS: PENGARUH MODEL PEMBELAJARAN MURDER BERBANTUAN ICE BREAKING DITINJAU PADA MINAT BELAJAR SISWA - Fadila, Abi; Kurniawan, Endi; Mujib (Program Studi Pendidikan Matematika FIP UNHASY, 2023)
This study aims to determine the difference in understanding mathematical concepts between classes taught with the MURDER learning model (Mood, Understanding, Recall, Digest, Expend, and Review) assisted by Ice Breaking and conventional learning in class XI students of SMK Negeri 1 Seputih Surabaya. This type of research is Quasy Experimental Design using a 2Ã—3 factorial research design. The samples used were students of class XI Accounting 1 and XI Accounting 2 SMK Negeri 1 Seputih Surabaya. This study also uses Cluster Random Sampling as a sampling technique, as well as for data collection, namely through tests. The data analysis technique was carried out quantitatively by using the Two Way ANOVA Test (Two-Way Variance Analysis). Through the calculation of the hypothesis, the results obtained that the p-Value value of the Ice Breaking-assisted MURDER learning model = 0.000 less than = 0.05 so that the p-Value , it can be said that there is an effect of using the Ice Breaking-Assisted MURDER learning model on the ability to understand students' mathematical concept .